EDUCATIONAL FINANCIAL MANAGEMENT : (Educational Investment Analysis) - Yuspiani; Hidayat, M. (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The purpose of this study is to analyze and examine the financial management of education from a critical point of view, especially regarding how much the analysis of the benefits of education costs as one of the considerations in making investment policies. The research method used is qualitative with a library research approach, from the data that has been collected and analyzed, the results show that quality education is expensive. The high cost of education requires effective and efficient financial management so that it can be used as one of the considerations in making investment decisions. The investment decisions taken indicate that the education costs incurred have benefits. The cost benefit analysis of education is represented in the form of a rasio between the present value of the costs and the present value of the benefits that will be obtained in the future. One the other hand. The high cost of education indicates the existence of privatization in the field of education which has resulted in educational institutions having the autonomy to determine their own cost of providing education, for that some parents of students need to understand the analysis of the benefits of education costs before taking investment policies in the education sector for the future of their children.